Composting Enhanced Manganese-Induced Sweet Potatoes Production in Sandy Soil - Md Sarwar, Jahan; Khairi, M; Nozulaidi, M; Syazwani, N (2016)
Composting retains different concentrations of nutrients, which are important in increasing health of sandy soil for sustainable production of crops. To examine the effects of compost on manganese (Mn)-induced sweet potato production, different plants parameters of sweet potato were measured. A foliar application of diverse concentrations of Mn (0.0, 0.2, 1.5 and 3.0 ppm) with or without composting was justified for the growth and development of sweet potato plants. Compost enhanced leaf area, chlorophyll (Chl) content, relative water content (RWC)of leaves, moisture content of the tuber, photosynthesis rate, tuber numbers, tuber weight, the content of ash, crude fiber, protein of tuber regardless of Mn application. Manganese concentration at 1.5ppm showed improved results of above parameters compared to the control and other concentrations of Mn. These results indicate that composting might increase the health of sandy soil, which endure the production of sweet potato in low fertile soil